Dynamic thermal simulation of ground heat exchangers for renewable heating of buildings - Gan, Guohui (2016)
The temperature of deep soil is relatively stable throughout a year and the thermal energy stored in soil can be used to provide renewable heat or coolth for a building. A ground heat exchanger is required to transfer heat between the fluid in the heat exchanger and surrounding soil. The control volume method is used to solve the equations for coupled heat and moisture transfer in soil and the dynamic interactions between the heat exchanger, soil and atmosphere. The method is used for numerical simulation of the dynamic thermal performance of horizontally coupled heat exchangers, taking account of dynamic variations of climatic, load and soil conditions. The thermal performance is compared for two types of ground heat exchangers - earth-liquid heat exchanger for a ground source heat pump and earth-air heat exchanger for ventilation. The amount and rate of heat transfer through an earth-liquid heat exchanger are larger than those for an earth-air heat exchanger and their differences increase with the length of heat exchanger and operating time.